2014
DOI: 10.3762/bjoc.10.81
|View full text |Cite
|
Sign up to set email alerts
|

Aza-Diels–Alder reaction between N-aryl-1-oxo-1H-isoindolium ions and tert-enamides: Steric effects on reaction outcome

Abstract: SummaryThe synthesis of 5-substituted 6,6a-dihydroisoindolo[2,1-a]quinolin-11(5H)-ones via [4 + 2] imino-Diels–Alder cyclization from N-aryl-3-hydroxyisoindolinones and N-vinyl lactams under Lewis acid-catalysed anhydrous conditions is reported. Reactions of N-(2-substituted-aryl)-3-hydroxyisoindolinones with N-vinylpyrrolidone under identical conditions resulted in the formation of 2-(2-substitued-aryl)-3-(2-(2-oxopyrrolidin-1-yl)vinyl)isoindolin-1-one analogues indicating steric hinderance as the cause of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Using the same type of dienophiles, Cameron and co-workers developed a method for the regioselective synthesis of isoindolo­[2,1- a ]­quinolone derivatives 482 starting from N -aryl-3-hydroxyisoindolinones 480 and dienophiles 481 via an in situ generated N -acyliminium ion intermediate in the presence of BF 3 ·OEt 2 (Scheme ). The reaction afforded exclusively the endo -products, where the hydrogen atoms on the stereogenic centers are in a cis -orientation with respect to each other.…”
Section: Synthesis Of 1234-tetrahydroquinolines Via the Povarov Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the same type of dienophiles, Cameron and co-workers developed a method for the regioselective synthesis of isoindolo­[2,1- a ]­quinolone derivatives 482 starting from N -aryl-3-hydroxyisoindolinones 480 and dienophiles 481 via an in situ generated N -acyliminium ion intermediate in the presence of BF 3 ·OEt 2 (Scheme ). The reaction afforded exclusively the endo -products, where the hydrogen atoms on the stereogenic centers are in a cis -orientation with respect to each other.…”
Section: Synthesis Of 1234-tetrahydroquinolines Via the Povarov Reactionmentioning
confidence: 99%
“…242 Using the same type of dienophiles, Cameron and co-workers developed a method for the regioselective synthesis of isoindolo [ of BF 3 •OEt 2 (Scheme 130). 243 The reaction afforded exclusively the endo-products, where the hydrogen atoms on the stereogenic centers are in a cis-orientation with respect to each other.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…17 This method relied on the use of an inexpensive organic triplet sensitizer (isopropylthioxanthone, ITX) as In(OTf) 3 In 2014, Jha and co-workers published their research on the aza-Diels-Alder between N-acyliminium ions and tertiary enamides. 20 The authors reported the synthesis of isoindoloquinoline derivatives 62 by reaction of N-aryl-3-hydroxyisoindolinones 60 and tertiary enamides 61 under anhydrous Lewis acid conditions using a stoichiometric amount of BF 3 •OEt 2 (Scheme 10A). It is interesting to note that only the endo-cycloadducts were obtained during the reaction in modest to good yields.…”
Section: Short Review Syn Thesismentioning
confidence: 99%
“…investigations support a non-concerted mechanism for the Lewis acid catalysed aza DA reaction. [33][34][35][36] In our previous work on AIIQ products 4a-m we mentioned that amide formation (g-lactamization) may occur directly aer aldimine formation and prior to [4 + 2] cycloaddition of the acyliminium intermediate. 15 In this present study, in order to elucidate this mechanistic route, we achieved isolation of Nphenyl-3-hydroxy-isoindolinone (A) under the same reaction conditions (see ESI †).…”
Section: Chemistrymentioning
confidence: 99%